Anonymous
Anonymous asked in Science & MathematicsMathematics · 1 decade ago

slove 2h^2-h-3=0 using zero factor property?

show work pls

2 Answers

Relevance
  • 1 decade ago
    Favorite Answer

    2h^2-h-3=0

    Factor:

    (2h - 3)(h + 1) = 0

    Use zero factor property twice:

    2h - 3 = 0

    2h = 3

    h = 3/2

    h + 1 = 0

    h = -1

  • PETER
    Lv 7
    1 decade ago

    By inspection the answer has the form

    (2h - 3)(h + 1)

    I then use FOIL to check:

    First terms 2h^2

    Outside Terms 2h

    Inside Terms -3h

    Last terms -3

    Collecting terms 2h^2 + 2h - 3h -3

    or 2h^2 - h -3

Still have questions? Get your answers by asking now.